Модель реалізації педагогічних умов формування готовності майбутніх тренерів зі східних одноборств до професійної діяльності у дитячо-юнацьких спортивних школах - Кузнецова, І. Ю.; Kuznetsova, I. Yu. (Virtus: Scientific Journal. – 2018. – № 29 (December). – Р. 42-46, 2018)
У статті визначено педагогічні умови формування готовності майбутніх тренерів зі східних одноборств до професійної діяльності у дитячо-юнацьких спортивних школах. Проаналізовано особливості професійної діяльності тренера, які вимагають формування готовності до її здійснення. Представлена модель реалізації педагогічних умов формування готовності майбутніх тренерів зі східних одноборств до професійної діяльності у дитячо-юнацьких спортивних школах.

The article defines the pedagogical conditions for the formation of readiness of future eastern martial arts coaches for professional activity in children and juniors sports schools. The features of the professional coach activity, which require formation of readiness for its implementation, are determined. The model of realization of pedagogical conditions for the formation of future eastern martial arts coaches for professional activity in children and juniors sports schools is presented. The data which are obtained during the research during the control phase of the experiment is given. Systematization and a generalized analysis of the results of the experimental study showed the effectiveness of the determined and implemented pedagogical conditions for the formation of the readiness of of future eastern martial arts coaches for professional activity in children and juniors sports schools.

В статье определены педагогические условия формирования готовности будущих тренеров по восточным единоборствам к профессиональной деятельности в детско-юношеских школах. Проанализированы особенности профессиональной деятельности тренера, которые требуют формирования готовности к ее осуществлению, представлена модель реализации педагогических условий формирования.
Model of realization of pedagogical conditions for the formation of future eastern martial arts coaches readiness to professional activity in children and juniors sports schools
Кузнецова, І. Ю. Модель реалізації педагогічних умов формування готовності майбутніх тренерів зі східних одноборств до професійної діяльності у дитячо-юнацьких спортивних школах / Кузнецова І. Ю. // Virtus: Scientific Journal. – 2018. – № 29 (December). – Р. 42-46.
Keywords: Освіта. Педагогіка. Education. Pedagogy. Образование. Педагогика; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; педагогічні умови; педагогические условия; pedagogical conditions; професійна діяльність; профессиональная деятельность; professional activity; професійна готовність; профессиональная готовность; professional readiness; тренери зі східних одноборств; тренеры по восточным единоборствам; eastern martial arts coaches; Фізична культура. Спорт. Physical Education. Sport. Физическая культура. Спорт